Gourava descriptors of multi‐dimensional flat and stable tri‐hexagonal boron nanotubes. Issue 2 (21st October 2021) - Shaker, Hani; Zobair, Mian Muhammad; Mehmood, Hafiz Muhammad Asif; Malik, Mehar Ali
Abstract: Gourava indices of boron nanotubes (BNT) are used to study the physical and electronic properties of nano semiconductor devices. Gourava indices have an important role in the study of high thermal conductivity and nano‐scale mechanical properties of semiconductors. These indices are also used to study the applicability of BNTs in the field of energy storage, and biomedical medicines. Since BNT like carbon nanotubes have almost the same tubular structure obtained by replacing carbon atoms with boron atoms. Therefore, they require theoretical study to establish structural changes in BNTs. In this paper, we compute the first and second Gourava descriptors, first and second hyper Gourava descriptors, sum and product connectivity Gourava descriptors and general first and second Gourava descriptors for the tri‐hexagonal BNTs. Abstract : Boron nanotubes are highly stable, flat, and metallic in nature and widely used in nano structured electronic devices. Boron nanotubes are much attractive due to their unique structure and appearance of multicenter bonds. Topological descriptors are the numeric quantities that associate the synthetic structure with different actual properties of substance, chemical reactions of substance, or organic action mathematically. Keeping in view the importance of Boron tubes, we computed Gourava descriptors, hyper Gourava descriptors, sum, and product connectivity Gourava descriptors and general first and second Gourava descriptors for the tri‐hexagonal boron nanotubes.